Pengaruh Debt to Equity Ratio, Return On Asset, Net Profit Margin Terhadap Harga Saham Perusahaan yang Tergabung dalam Indeks Bisnis 27 - Istifani Sucimanah; Dedi Hariyanto; Heni Safitri (Universitas Muhammadiyah Pontianak, 2018)
The purpose of this research is to know the influence of Solvability using Debt to Equity Ratio (DER), Profitability using Return on Asset (ROA) and Net Profit Margin (NPM) to the stock price of a company incorporated in Business Index 27. Sampling technique used in this study is a full sample method. The sample in this research is 27 companies. Analytical techniques used are normality test, multicollinearity, autocorrelation, heteroscedasticity, linearity, multiple linear regression, multiple correlation coefficient (r), the coefficient of determination (R2), hypothesis testing simultaneously by using F test and partially by using t-test.The results of the normality test show all standard distributed data with asymp. Sig. (2-tailed) Unstandardized Residual of 0.188 is higher than 0.05. For simultaneous test results using F, the test shows that the three independent variables DER, ROA, NPM together have no significant effect on the dependent variable (stock price) proved from the value of F arithmetic of 0.191 and had a sig value. Of 0.901 which is higher than 0.05. The result of the partial test by using t-test shows that the three independent variables DER, ROA, NPM has no significant effect on the dependent variable (stock price) proven from the value of t arithmetic DER of 0,531 and has the sig value of 0.600 is more significant than 0.05, the amount of t count ROA of -0.647 and has a sig value. Of 0.524 is higher than 0.05 and the importance of t arithmetic NPM of -0.680 and has a sig value of 0,503 which is higher than 0.05